Integrated network pharmacology and experimental analysis unveil multi-targeted effect of 18α- glycyrrhetinic acid against non-small cell lung cancer - Irshad, Rasha; Raj, Nafis; Gabr, Gamal A.; Manzoor, Nikhat; Husain, Mohammad (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC) is one of the most malignant types of cancer with soaring incidence rates worldwide, attributed to its heterogeneity and complex etiology. Evidently, alternative anti-cancer therapies comprising traditional medicines and natural products have gained attention for their ability to act as chemopreventive agents with minimal toxicities, either alone or in combination. Accumulating studies have substantiated the inevitability of network pharmacology studies for effectively mapping molecular targets of natural products against multifaceted diseases, including cancer. The 18α-Glycyrrhetinic acid (18α-GA), a triterpenoid found in licorice plants, has shown promising medicinal properties, although, its mechanism of action against NSCLC yet remains elusive. The present study was conducted to explore the anti- NSCLC potential of 18α-GA, employing integrative network pharmacology, molecular docking, and experimental research. Initially, network analysis revealed 181 common targets of 18α-GA in NSCLC as shown in the “compound- target- disease” network employing Cytoscape 3.8.2. Further analyses identified EGFR, AKT1, PI3KR1, MAPK1, IGF1, and SRC as the most crucial hub targets of 18α-GA against NSCLC. Moreover, molecular docking simulations and functional enrichment analyses indicated the involvement of multiple signaling pathways in suppressing NSCLC. Subsequent in-vitro studies verified the anti-proliferative effect of 18α-GA on two NSCLC cancer cell lines, H1299 and A549. Mechanistically, 18α-GA arrested cell cycle at the G1 phase, induced apoptosis, decreased migratory potential, and protein expression levels of EGFR-PI3K/AKT, as examined by flow cytometry, morphological assessment, RT-PCR, and western blot. In conclusion, this study delineates the therapeutic potential and underlying mechanism(s) of 18α-GA as a putative novel drug against NSCLC. However, further studies are warranted to elucidate the complete molecular mechanism(s) using animal models of NSCLC.